Adubação nitrogenada sobre o crescimento, a produção e a qualidade de gramíneas forrageiras tropicais - Castagnara, Deise Dalazen (2009)
The experiment was developed in the experimental farm "Professor Antonio Carlos dos Santos Pessoa", in an experimental area of the Center of Agrarian Sciences, of Oeste Paraná's State University - Campus Marechal Cândido Rondon in a Red Latosol, with the objective evaluates the application of growing doses of nitrogen (N) on three tropical forages. The design used were randomized complete block in factorial outline 4x3 (four doses of N (0; 40; 80 and 160 kg ha-1) and three tropical forage grasses (Panicum maximum cv. mombaça, Panicum maximum cv. Tanzania and Brachiaria hybrid sp Mulato)), with three repetitions. The evaluations were initiate in December of 2008, after the standardization cut and application of the fertilization nitrogen. The morphogenic characteristics were obtained by the technique of demarcation of the tillers, while the structural and productive characteristics were appraised in the occasion of the cut that was accomplished with regrowth age of 42 days. The bromatological composition was determined in the material sampled by occasion of the cut. The effect of doses of nitrogen was compared through regression analysis and, for choice of the model, was considered significance of 5% for the coefficients of the equations and the determination coefficient. The forages were compared by Tukey test to 5% of probability. The emergence taxes and prolongation of leaves presented positive lineal answer to the doses of N, while the phyllochron answered in a negative lineal way, with the superiority of the tanzania and mombaça grasses. There were not significant effect of the doses of N, grasses and interaction about the duration of life of the leaves and on the senescência tax to foliate. There was quadratic effect of the doses of N on the tax of prolongation of stems, the final length of leaves, and the height of the dossal with the superiority of the tanzania and mombaça grasses. The number of alive leaves for tiller presented positive lineal behavior in response to the doses of N, while the perfilhos density presented quadratic behavior. For the perfilhos density there was effect of the interaction, and the mulato grass presented density of superior perfilhos to the others. Effect lineal negative of the doses of N was detected on the variable relationship leave/stem. The diameter of the base of the stem was only influenced by the grasses. For the productions of matter total drought, of leaves and of stems significant effect of the doses of N was verified, of the foragers and of the interaction. As for the nutritional composition, for the tenor of crude protein (CP) significance of the interaction of the factors was verified, while the tenors of fiber neutral detergent (FND) answered from a quadratic way to the doses of N. The tenors of fiber acid detergent (FAD) were influenced just by the grasses. There was significant effect of the doses of N and of the interaction on the tenors of mineral matter. The manuring nitrogen influenced positively most of the morphogenic, structural, productive and nutritional characteristics studied, suggesting that his use can be beneficial to elevate the productive indexes and to improve the nutritional quality of the pastures